Functional Identification and Characterization of the Diuretic Hormone 31 (DH31) Signaling System in the Green Shore Crab, Carcinus maenas - Alexander, Jodi; Oliphant, Andrew; Wilcockson, David C.; Webster, Simon G. (Frontiers in Neuroscience, 2018)
The functional characterization of crustacean neuropeptides and their cognate receptors has not kept pace with the recent advances in sequence determination and, therefore, our understanding of the physiological roles of neuropeptides in this important arthropod sub-phylum is rather limited. We identified a candidate receptor-ligand pairing for diuretic hormone 31 (DH31) in a neural transcriptome of the crab, Carcinus maenas. In insects, DH31 plays species -specific but central roles in many facets of physiology, including fluid secretion, myoactivity, gut peristalsis and circadian rhythms of behavior. The DH31 transcript codes for a 147 amino acid prepropeptide, and a single receptor transcript translates to a secretin-like (Class B1) G-protein coupled receptor (GPCR). We used an in vitro aequorin luminescence Ca2+ mobilization assay to demonstrate that this candidate DH31R selectively binds, and is activated by, Carcinus and insect DH31s in a dose-dependent manner (EC50 15-30nM). Whole mount immunohistochemical and in-situ hybridization localization revealed extensive DH31 expressing neurons throughout the central nervous system, most notably in the abdominal ganglion where large, unpaired cells give rise to medial nerves, which terminate in extensive DH31 immunopositive dendritic fields intimately associated with oesophageal musculature. This system constitutes a large and hitherto undescribed neurohemal area adjacent to key muscle groups associated with the gastric system. DH31 expressing neurons were also seen in the cardiac, commissural, oesophageal and stomatogastric ganglia and intense labeling was seen in dendrites innervating fore- and hindgut musculature but not with limb muscles. These labeling patterns, together with measurement of DH31R mRNA in the heart and hindgut, prompted us test the effects of DH31 on semi-isolated heart preparations. Cardiac superfusion with peptide evoked increased heart rates (10-100nM). The neuroanatomical distribution of DH31 and its receptor transcripts, particularly that associated with gastric and cardiac musculature, coupled with the cardio- acceleratory effects of the peptide implicate this this peptide in key myoactive roles, likely related to rhythmic coordination. We discuss the notion that DH31 may contribute to the stereotyped muscle contractions associated with exuviation during ecdysis.